Noninvasive Assessment Of Cardiovascular Autonomic Dysfunction In Patients With Type 2 Diabetes Melitus - DIPTI MOHAPATRA; PRAKASH KUMAR SASMAL (International Journal of Pharma and Bio Sciences, 2012)
Diabetes mellitus is one of the most leading public health problems in the world. It affects almost all the body systems, especially the nervous and the cardiovascular system. Cardiac Autonomic Neuropathy (CAN) is the clinically important form of Diabetic Autonomic Neuropathy, associated with increased mortality. Again, CAN is the most overlooked complication of diabetes. Hence assessment of cardiovascular reflexes affords a satisfactory method for evaluation of CAN.The present study was undertaken to assess the cardiovascular dysfunction in patients of type 2 diabetes mellitus by the use of simple noninvasive tests proposed by Ewing & Clarke. The tests which were done were heart rate response to Valsava, heart rate response to deep breathing and heart rate response to standing, blood pressure response to standing and blood pressure response to a sustained hand grip. Patients of Type 2 Diabetes Mellitus showed abnormal responses to the above tests as compared to controls.